Desenvolvimento de um artefato para avaliação da maturidade digital em universidades Públicas: aplicação na UFMT - Silva, Thais Fernanda Bueno da (Universidade Federal de São Carlos, 2025)
Digital transformation is an essential process for the modernization of the public sector, promoting improvements in efficiency, transparency, and service delivery. However, the absence of standardized and empirically validated methods hinders the assessment of digital maturity in public organizations. This study has the general objective of adapting a digital maturity assessment model for federal higher education institutions, considering the guidelines of Brazilian Law No. 14,129/2021 on Digital Government. The research adopts a methodological approach structured in three stages: (a) a systematic literature review of digital maturity methods applicable to public administration; (b) the application of an assessment method adapted to the institutional context of FUFMT, through a questionnaire; and (c) the development of a guiding framework to support public higher education institutions in diagnosing and advancing digital maturity. The expected results include the identification of gaps in existing methods, the mapping of the most relevant dimensions, and the proposal of strategic recommendations to strengthen digital transformation in public educational institutions.
Development of an artifact for assessing digital maturity in public universities: an application at UFMT
Keywords: Maturidade Digital; Transformação Digital; Administração pública; IFES; Revisão Sistemática; Governança Digital; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO; 9. Indústria, Inovação e Infraestrutura